Through the Looking Glass: The Queer Narcissism of Selfies - Greg Goldberg (Social Media + Society, 2017)
A number of scholars have recently argued that the selfie needs to be understood outside of the discourse of narcissism. Rather than leaving this discourse behind, this article focuses on the “hype” of selfies as narcissistic in order to identify and ultimately trouble the political unconscious of this diagnosis, and to ask, what is the problem of narcissism such that it can serve as a means of devaluing, and what kind of politics might we find in the behaviors, proclivities, or attributes identified as narcissistic? The article argues that the problem of narcissism is less an exaggerated focus on the self than it is a failure of responsibility for oneself, and/or an insufficient concern for the well-being of others to whom the narcissist ought to be responsible. Drawing from the antisocial thesis in queer theory, the article argues that this normative investment in responsible subjectivity is motivated, rather ironically, by a desire to annihilate difference. As a “solution” to this desire, the article offers queer theorist Leo Bersani’s notion of “impersonal narcissism,” which it understands in relation to the queerness of the myth from which narcissism takes its name. In short, the article does not aim to evaluate empirically attributions of selfie narcissism—whether to confirm or falsify—but rather to problematize the diagnosis of narcissism as rooted in a normative project that works to produce responsible subjects, and to suggest that this project is compromised by a queer indifference to difference, as critics fear.